Corruption criminal offences: concept and classification - R. I. Login (Bulletin of Kharkiv National University of Internal Affairs)
The article highlights modern scientific approaches to the definition of the concept and classification of corruption criminal offences, as well as their general characteristics. The emphasis is placed on the unresolved issue of distinguishing between the signs of corruption and the signs of a corruption offence. The original author's position is expressed that corruption offences are endowed with corruption features which allow distinguishing them from other criminal offences and subjecting them to grouping. The position that corruption criminal offences are characterised by the general features of all criminal offences provided for by the Criminal Code of Ukraine without exception has been supported, along with which specific features should be distinguished, i.e. those which characterise only the category of corruption criminal offences. In particular, they include: abuse of office; presence of a mandatory object – an unlawful benefit; special subject, which is an official of public or private law, regardless of the legal form and form of ownership, as well as a person providing public services; presence of only a deliberate form of guilt, namely direct intent; special purpose of committing a socially dangerous act. Corruption criminal offences are also classified on the basis of the generic object of the criminal offence: corruption criminal offences against property, in the field of economic activity, against public security, in the field of trafficking in narcotic drugs, psychotropic substances, their analogues or precursors, against the authority of state authorities, local self-government bodies and associations of citizens, in the field of official activity and professional activity related to the provision of public services, against the established procedure for military service.